Integration of the circular economy into the food industry - Kostiuk, M. V.; Костюк, М. В. (Запоріжжя: ТДАТУ, 2025)
The food industry is one of the largest consumers of natural resources and simultaneously one of the key generators of waste and greenhouse gas emissions worldwide. According to international organizations, up to one third of all food produced is lost or wasted at various stages of the “farm-tofork” supply chain, leading to significant economic losses and environmental risks [2; 5; 6].
Keywords: food industry; farm-tofork